2016
DOI: 10.1515/jas-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Starch Syrups for Winter Feeding of Honeybee Colonies

Abstract: A b s t r a c t :Three different starch syrups available on the Polish market for winter feeding of bees were evaluated for two consecutive beekeeping seasons (2012/2013 and 2013/2014). Sugar syrup and inverted sucrose syrup were used as the control. Winter feeding was conducted at two times: earlier and later in the season. After supplementation of winter feeding was stopped, we measured colony strength (number of combs covered by bees) and brood area. After overwintering (spring 2013 and 2014), we estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Semkiw and Skubida ( 2016 ) conducted a study on five different syrups as bee feeds in the winter of 2012–2013 and 2013–2014 with respect to feed consumption, colony strength and development dynamics, honey yield from spring flow and bee mortalities. The feeds analysed where three commercial starch syrups (Apifood ‐ from Poland, Apikel 20‐ from Germany, Apifortune ‐ from France), one commercial inverted sucrose syrup (Apiinvert ‐ from Germany) and a home‐made syrup (sucrose to water ratio 5:3).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Semkiw and Skubida ( 2016 ) conducted a study on five different syrups as bee feeds in the winter of 2012–2013 and 2013–2014 with respect to feed consumption, colony strength and development dynamics, honey yield from spring flow and bee mortalities. The feeds analysed where three commercial starch syrups (Apifood ‐ from Poland, Apikel 20‐ from Germany, Apifortune ‐ from France), one commercial inverted sucrose syrup (Apiinvert ‐ from Germany) and a home‐made syrup (sucrose to water ratio 5:3).…”
Section: Assessmentmentioning
confidence: 99%
“…In the study from Van der Zee andPisa (2010, 2011), the colony collapse seen in the Netherlands was attributed to a combination of starvation of bees because of crystallised bee feed and high HMF contents in bee feed. Semkiw and Skubida (2016) found that concentrations of up to 40 mg HMF/kg bee feed had no adverse effects on colonies, and Kozianowski (2016) concluded that feeding of bees with concentrations of up to 150 mg HMF/kg bee feed had no adverse effects on colonies. The CONTAM Panel noted that field studies are more likely to reflect the real situation as compared to laboratory studies with an artificial and standardised setting and with a relatively low number of animals.…”
Section: Chronic Effectsmentioning
confidence: 99%
“…Carbohydrate-rich supplementary food provides an alternative source of energy, increases colony strength, prevents starvation, and may reduce wintering losses (Emsen and Dodologlu 2014). A mixture of sucrose and water is commonly used to feed honey bee colonies that do not have sufficient stores to survive during winter (Free and Spencer-Booth 1961;Barker 1971;Semkiw and Skubida 2016); in fact, in temperate areas, supplementary feeding usually occurs in the autumn period, when honey bees may suffer from low nectar flow and bad weather conditions. The most common diet for supplementary feeding consists in inverted sugar syrup obtained by mixing sugar and water in a 2:1 ratio to which a variable amount of an acidifying agent is added (Bailey 1966;Standifer et al 1977;Genc and Aksoy 1993); very often, beekeepers produce this food themselves, boiling a water sugar solution acidified with vinegar or lemon juice.…”
Section: Introductionmentioning
confidence: 99%
“…However, a responsible approach to bee health requires that also the possible detrimental side effects of any intervention, including supplementary nutrition, are investigated. This issue was considered for some types of sugar syrup as HFCS, starch syrups and inverted sugar syrup and sugar candy (Barker and Lehner 1978;Rinderer and Baxter 1980;Severson and Erickson 1984;Von der Ohe and Schönberger 2002;Ceksteryte and Racys 2006;LeBlanc et al 2009;Sammataro and Weiss 2013;Smodiš Škerl and Gregorc 2014;Semkiw and Skubida 2016). However, despite the use of 2:1 sucrose-water sugar syrup is very common (Bailey 1966;Standifer et al 1977;Genc and Aksoy 1993), only limited scientific information is available on its possible side effects.…”
Section: Introductionmentioning
confidence: 99%